Investigation of AC-Measurements of Epoxy/Ferrite Composites - Moustafa A. Darwish; Alex V. Trukhanov; Oleg S. Senatov; Alexander T. Morchenko; Samia A. Saafan; Ksenia A. Astapovich; Sergei V. Trukhanov; Ekaterina L. Trukhanova; Andrey A. Pilyushkin; Antonio Sergio B. Sombra; Di Zhou; Rajshree B. Jotania; et al. (Nanomaterials, 2020)
A pure ferrite and epoxy samples as well as the epoxy/ferrite composites with different 20 wt.%, 30 wt.%, 40 wt.%, and 50 wt.% weight ferrite contents have been prepared by the chemical co-precipitation method. AC-conductivity and dielectric properties such as the dielectric constant and dielectric loss of the prepared samples have been studied. The obtained results showed that the samples had a semiconductor behavior. The dielectric constant of the composites has been calculated theoretically using several models. For the composite sample that contains 20 wt.% of ferrites, these models give satisfactory compliance, while for the composite samples with a higher percentage of nanofillers, more than 30 wt.% theoretical results do not coincide with experimental data. The investigated polymer has very low conductivity, so this type of polymer can be useful for high-frequency applications, which can reduce the losses caused by eddy current. Thus, the prepared samples are promising materials for practical use as elements of microwave devices.